Green Behaviour of The Customers of Four-Wheeler Automobiles - An Application of Dummy Variable Regression Model - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
To analyse the factors affecting the Green purchasing behaviour of the customers of four-wheeler automobiles in Kerala.